Correlates of suicidal ideation related to the COVID-19 Pandemic: Repeated cross-sectional nationally representative Canadian data. (December 2021) - McAuliffe, Corey; Pumarino, Javiera; Thomson, Kimberly C.; Richardson, Chris; Slemon, Allie; Salway, Travis; Jenkins, Emily K.
Abstract: Objective: With significant levels of mental distress reported by populations, globally, the magnitude of suicidal ideation during and beyond the COVID-19 pandemic is a central concern. The goal of this study was to quantify the extent of pandemic-related suicidal ideation in the Canadian population during the first ten months of the pandemic and identify sociodemographic and pandemic-related stressors associated with increased risk of ideation. Method: Data were derived from three rounds of a mental health monitoring survey, nationally representative by age, gender, household income, and region, delivered online in May 2020, September 2020, and January 2021. Bivariate analyses were used to quantify the proportion of respondents in Canada reporting suicidal ideation by sociodemographic factors and pandemic-related stressors. Unadjusted and adjusted multivariable logistic regression was used to study the association between suicidal ideation and correlates within four pandemic-related stressor categories (financial, relationship, substance use, COVID-19 exposure). Results: Of the 7002 respondents, 6.2% (n = 433) reported experiencing suicidal thoughts or feelings as a result of the pandemic within the two weeks prior to taking the survey. In terms of sociodemographic factors, suicidal ideation was more commonly reported among those who were not cisgender, <65 years-old, single, Indigenous, LGBT2Q+, and who experience a pre-existing mental health condition. After adjusting for sociodemographic factors, indicators across all four pandemic-related stressor categories were associated with two or more times the odds of suicidal ideation. Conclusion: Disparities in COVID-19 related suicidal ideation have persisted throughout the first year of the pandemic for specific sociodemographic sub-groups and those who have faced stressors related to finances, relationships, increased substance use, and COVID-19 virus exposure. To best address these disparities and to prevent a transition from suicidal ideation to action, appropriate planning, resources, and policies are needed to ensure health and well-being for everyone. Highlights: 6.7% of respondents reported experiencing suicidal thoughts/feelings due to the pandemic. Proportion of Canadians experiencing suicidal thoughts/feelings has increased. Sociodemographic characteristics associated with higher odds of suicidal ideation. Stressors related to finances, relationships, increased substance use, and COVID-19 exposure.